Obesity and its impact on female reproductive health: unraveling the connections - Zheng, Lei; Yang, Lixian; Guo, Ziru; Yao, Nan; Zhang, Shiyu; Pu, Pengpeng (Frontiers in Endocrinology, 2024)
In the modern era, the escalating global prevalence of obesity has profound implications on female reproductive health. Obesity, transcending mere lifestyle choices, has evolved into a complex disorder affecting physiological and metabolic functions. Concurrently, female infertility is rising as a significant global health issue. Obesity, with its extensive systemic effects, is pinpointed as a major disruptor. The convergence of these health challenges reveals a multifaceted scenario: on one hand, obesity directly impacts female reproductive health, particularly in the context of conditions like polycystic ovary syndrome (PCOS) and menstrual disturbances; on the other, the psychosocial consequences of infertility might intensify weight-gain patterns, forming a challenging cycle. Additionally, the economic implications of treating obesity-related infertility are considerable. This review delves into the myriad ways obesity affects female reproductive health, drawing insights from epidemiological, clinical, and molecular studies. It explores the epidemiological relationship between obesity and PCOS, the influence of obesity on menstrual disturbances, and the broader impact of obesity on female infertility. Weight loss, through pharmacological interventions, surgical methods, or lifestyle adjustments, emerges as a promising strategy. Lastly, the efficacy of assisted reproductive technologies, such as IVF, is influenced by obesity, underscoring the importance of an optimal body mass index. The review also highlights the molecular and physiological mechanisms underlying the impact of obesity on female reproductive health, including the disruption of the hypothalamic-pituitary-ovary axis, altered adipokine secretion, and the role of chronic inflammation and oxidative stress.